Sea Grant Programs Build Resilience to Coastal Climate Hazards - Ian Miller; Mary Collins; Michelle Covi; Parker Gassett; Holly Abeels; Karina Alvarez; Juliana Barrett; Savanna Barry; Mona Behl; Renee Collini; Laura Engeman; Phyllis Grifman; et al. (Oceanography, 2024)
Sea Grant programs across the United States and its territories are working with coastal communities to enhance their resilience to hazards and weather extremes exacerbated by climate change. Drawing on the expertise of the authors, many of whom have multiple years or decades of experience in the Sea Grant network, the article identifies five key strategies that Sea Grant programs employ to support the process of coastal hazards and extreme weather adaptation and resilience-building. The application of these strategies, most of which have their roots in the historical legacy of extension, are then illustrated through summaries of current Sea Grant activities and projects, showcasing how they have been applied in real-world situations. These strategies allow Sea Grant programs to fill a unique and valuable niche in national efforts to enhance coastal resilience. The article concludes with a discussion of emerging challenges and recommendations for strengthening Sea Grant’s capacity to support adaptation in coastal communities into the future.

An early warning system for wave-driven coastal flooding at Imperial Beach, CA - Mark A. Merrifield; Mele Johnson; R. T. Guza; Julia W. Fiedler; Adam P. Young; Cassandra S. Henderson; Athina M. Z. Lange; William C. O’Reilly; Bonnie C. Ludka; Michele Okihiro; Timu Gallien; Kyle Pappas; et al. (Natural Hazards, 2021)
Waves overtop berms and seawalls along the shoreline of Imperial Beach (IB), CA when energetic winter swell and high tide coincide. These intermittent, few-hour long events flood low-lying areas and pose a growing inundation risk as sea levels rise. To support city flood response and management, an IB flood warning system was developed. Total water level (TWL) forecasts combine predictions of tides and sea-level anomalies with wave runup estimates based on incident wave forecasts and the nonlinear wave model SWASH. In contrast to widely used empirical runup formulas that rely on significant wave height and peak period, and use only a foreshore slope for bathymetry, the SWASH model incorporates spectral incident wave forcing and uses the cross-shore depth profile. TWL forecasts using a SWASH emulator demonstrate skill several days in advance. Observations set TWL thresholds for minor and moderate flooding. The specific wave and water level conditions that lead to flooding, and key contributors to TWL uncertainty, are identified. TWL forecast skill is reduced by errors in the incident wave forecast and the one-dimensional runup model, and lack of information of variable beach morphology (e.g., protective sand berms can erode during storms). Model errors are largest for the most extreme events. Without mitigation, projected sea-level rise will substantially increase the duration and severity of street flooding. Application of the warning system approach to other locations requires incident wave hindcasts and forecasts, numerical simulation of the runup associated with local storms and beach morphology, and model calibration with flood observations.